Consumer profile of the new market segments: case of Saltillo, Coahuila (Revista de Investigaciones Universidad del Quindío, 2021)
Over time, marketers have used specialized segmentation techniques to find their target markets. Angus and Westbrook, (2018), (2019), (2020) and (2020) detail new customer profiles within global consumer trends.This work is intended to address the propensity of purchasing practices of Saltillo through an exploratory / descriptive study, with a quantitative approach and using descriptive statistics and factor analysis. Applying an instrument of forty-nine items, with a Likert-type response scale from 1 to 7. The sample is of 275 subjects aged 15 to 78 years in the city of Saltillo, Coahuila and the field work was carried out during the months January and February of the year 2020.The analysis carried out was that of the variance of one factor (ANOVA) in order to check if there are significant differences between each of the items that make up the scale.The results of the study allowed us to better understand the consumers currently emerging in the city of Saltillo, Coahuila.
Keywords: consumer behavior; segmentation; customer profiles; trends